2009
DOI: 10.1007/s11239-009-0371-x
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-based costs associated with venous thromboembolism prophylaxis regimens

Abstract: Clinically and economically, venous thromboembolic (VTE) disease represents a significant burden to the US healthcare system. This analysis compares the total direct medical costs associated with VTE prophylaxis with enoxaparin and unfractionated heparin (UFH). Hospital discharge and billing records were extracted from the Premier Perspective database (January 2002-December 2006). The primary outcome was the total direct medical costs for discharges that were at risk of VTE and received enoxaparin or UFH. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Previous studies, using hospital or payer information, have shown that VTE prophylaxis is more cost‐effective compared with no prophylaxis. In terms of the different VTE prophylaxis regimens, enoxaparin represents a more cost‐effective option in comparison with UFH19, 21, 29–32 and also when compared with fondaparinux 21, 33. When comparing the results between different trials, it should be noted that previous analyses were mainly modeled on the Prophylaxis in Medical Patients with Enoxaparin (MEDENOX) study, which was performed in general medical patients and reported a VTE rate of 5.5% 6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies, using hospital or payer information, have shown that VTE prophylaxis is more cost‐effective compared with no prophylaxis. In terms of the different VTE prophylaxis regimens, enoxaparin represents a more cost‐effective option in comparison with UFH19, 21, 29–32 and also when compared with fondaparinux 21, 33. When comparing the results between different trials, it should be noted that previous analyses were mainly modeled on the Prophylaxis in Medical Patients with Enoxaparin (MEDENOX) study, which was performed in general medical patients and reported a VTE rate of 5.5% 6.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective analysis of transactional billing records demonstrated that, despite higher mean costs of anticoagulation therapy, the mean, total, adjusted direct hospital costs were lower with LMWH thromboprophylaxis compared with UFH ($7358 vs $8680, respectively; difference $1322; P < 0.001) 21. A previous study by Burleigh and colleagues based on hospital discharge information extracted from both medical and surgical patients, has a sub‐analysis in patients with stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LMWH is an attractive treatment option as it is easily dosed and does not require regular blood tests to monitor levels required with UFH. Not only does this make it more convenient but it also has important cost implications [15,16]. Despite the current evidence supporting the use of LMWH instead of UFH in veno-occlusive conditions there is no current guidance in patients with peripheral arterial embolic disease.…”
Section: Introductionmentioning
confidence: 99%
“…7 In 1997, the total cost to the health economy in treating VTE related problems in the United States was estimated to be $1.5 billion/year. 8,9 The total cost of managing VTE in the United Kingdom is over £640 million (€798 million; $1.01 billion) annually. 10 Therefore emphasis must be placed on its prevention.…”
mentioning
confidence: 99%